Peripheral blood mononuclear cells isolated from patients with diabetic nephropathy show increased activation of the oxidative-stress sensitive transcription factor NF-kB - Hofmann Bowman, Marion; Schiekofer, Stephan; Isermann, Berend; Kanitz, Michael; Henkels, M.; Joswig, M.; Treusch, A.; Morcos, Michael; Weiss, T.; Borcea, Valentin; Abdel-Khalek, Mohamed; Amiral, Jean; et al. (Diabetologia, 1999)
Increased oxidative stress and subsequent activation of the transcription factor NF-kB has been linked to the development of late diabetic complications. To determine whether oxidative stress dependent NF-kB activation is evident in patients with diabetic nephropathy we used an Electrophoretic Mobility Shift Assay based semiquantitative detection system which enabled us to determine NF-kB activation in ex vivo isolated peripheral blood mononuclear cells.
Gesehen am 28.05.2021